(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2023)
As a synthesis between philosophical, psychological, biographical, and historical contexts, this paper explores the traumatic effects of post-colonialism on generations, focusing on a specific genre called "magical realism." By comparing two magical realist authors, one who won the Nobel Prize already (Gabriel García Márquez) and one who should (Isabelle Allende), this piece explores how the genre can serve as a coping mechanism for national trauma suffered by people in a post-colonial world. For additional context, listen to the author’s reflection on the piece below.